Spectral analysis of electromyograms in assessment of the functional state of the back muscles in degenerative diseases of the spine (literature review) - Skidanov, Artem; Dupliy, Diana; Kolesnichenko, Vera; Radchenko, Volodymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Review is devoted to the problem of the interrelation of osteochondrosis with changes of functioning of paravertebral muscles and electromyographic (EMG) assessment of their condition. There were used materials of specialized periodical issues in the last 30 years. EMG-examination allows to estimate not only the degree of muscle tension but also bioelectrical structure of generated tension. Provided that the development of pathological conditions of muscles they alter the number of functional motor units and consequently the frequency of pulses creating a distinctive look of a electromyography. Bioelectric changes in working muscle occur together with biochemical and physiological processes that can be considered as an objective assessment of physiological fatigue. In this paper there were described electrophysiological properties of the muscles, analyzed violations of their electrogenesis for various types of motor fatigue, considered the most informative parameters of electromyogams. Representation of interference myogram as a combination of periodic harmonics allows to apply mathematical models of analysis in particular Fourier or spectral analysis. This approach makes it possible to identify the essential components of the periodic activity of motor units. EMG-examination of the patients suffering with back pain and healthy individuals show increasing of muscle fatigue. After surgeries without fusion of functional spinal unit one may observe restoration of preoperative status of muscles operated. Spectral analysis makes it possible to observe the dynamic characteristics of muscle tension. The benefits of EMG include informational content of a frequency analysis in cases of either minimum stress or greater one which reduces the impact factor motivating the patient. Except this it allows to examine patients with pain syndromes. An indicator of fatigue is the median of frequency spectrum, and the most individual are starting median frequency and width of half a maximum of a spectrum.